(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study aims to analyze the relationship between strategic consensus in its two dimensions (alignment and strategic commitment) and digital entrepreneurship in its three dimensions Digital adventure, proactive competition, digital independence, and digital research and development) through the interactive role of creative thinking in its dimensions (flexibility, originality, problem solving, and fluency), in order to address the problem of the limited number of studies that investigated the relationship between these variables , especially in the Iraqi banking sector, which is witnessing a rapid digital transformation . Also, the study of creative thinking as an interactive variable in this relationship has not received sufficient attention in previous literature, which calls for verifying this role to support the theoretical and applied understanding of it.The importance of this study lies in bridging or reducing the knowledge gap between the aforementioned variables and providing applied insights for the bank under study.It is in line with the digital transformation. The researcher has distributed A specially prepared questionnaire For this purpose, a sample of employees of the Trade Bank of Iraq (TBI) in the branches of the Middle Euphrates Governorates (Babil, Karbala, Najaf) was recruited, numbering 135).employee,and then I get back( 116 A questionnaire valid for statistical analysis was analyzed using advanced statistical tests such as confirmatory factor analysis and structural equation modeling using Smart PLS v.4 software .and SPSS v.28 . The results showed a positive impact of strategic consensus on digital entrepreneurship, with this impact being enhanced in the context of the interactive role.For creative thinking, which requires the bank under study to enhance strategic consensus acrossTraining programs and development of policies that support digital leadership, developing creative thinking skills, and conducting broader studies to explore...Other variables with a potential impact on the banking sector in Iraq .